The Characteristics of Multilocus Sequence Typing, Virulence Genes and Drug Resistance of Klebsiella pneumoniae Isolated from Cattle in Northern Jiangsu, China - Tianle Xu; Xinyue Wu; Hainan Cao; Tianxu Pei; Yu Zhou; Yi Yang; Zhangping Yang (Animals, 2022)
Klebsiella pneumoniae (K. pneumoniae) induced bovine mastitis has been becoming one of the dominantly pathogenic bacteria in cases of bovine mastitis, and is threatening public health through dairy products. In order to explore the characteristics of multilocus sequence typing (MLST), virulence gene carrying, and the relationship between virulence genes and the antibiotic resistance of Klebsiella pneumoniae from dairy cattle in northern Jiangsu, 208 dairy milk samples were collected from four dairy farms in northern Jiangsu. A total of 68 isolates were obtained through bacterial isolation, purification, and 16S rDNA identification. Eleven virulence genes were detected by specific PCR. The susceptibility of the isolates to antimicrobials was analyzed using the Kirby–Bauer method. The Pearson correlation coefficient was used to analyze the correlation between the presence of virulence genes and the phenotype of drug resistance. ST 2661 was the most prevalent type of K. pneumoniae (13/68, 19.1%) among the 23 ST types identified from the 68 isolates. The virulence gene allS was not detected, but the positive detection rates of the virulence genes fimH, ureA, uge and wabG were 100.0%. Notably, the detection rates of genes rmpA and wcaG, related to the capsular polysaccharide, were 4.4% and 11.8%, respectively, which were lower than those of genes related to siderophores (kfuBC, ybtA and iucB at 50.0%, 23.5%, and 52.9%, respectively). The K. pneumoniae isolates were sensitive to ciprofloxacin, nitrofurantoin, and meropenem. However, the resistance rate to penicillin was the highest (58/68, 85.3%), along with resistance to amoxicillin (16/68, 23.5%). The results revealed the distribution of 23 ST types of K. pneumoniae from the milk from bovine-mastitis-infected dairy cows in northern Jiangsu, and the expression or absence of the virulence gene kfuBC was related to the sensitivity to antibiotics. The current study provides important information relating to the distribution and characteristics of K. pneumoniae isolated from dairy cows with clinical bovine mastitis, and is indicative of strategies for improving the treatment of K. pneumoniae-induced bovine mastitis.